2016
DOI: 10.3109/14017431.2016.1173226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholecalciferol supplementation on arterial stiffness: a systematic review and meta-analysis

Abstract: There was no improvement of markers of arterial stiffness after vitamin D supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
4
17
0
1
Order By: Relevance
“…On the other hand, trials assessing the effects of vitamin D supplementation on arterial stiffness, a marker of cardiovascular risk, have shown ambiguous results. In a MA including data from seven RCTs involving a total of 547 participants, supplementation with vitamin D3 for 2 to 12 months showed no significant effects on changes in pulse wave velocity [44]. Nor did a MA including data from seven RCTs suggest beneficial effects of vitamin D supplementation on left ventricular function or exercise tolerance [45].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, trials assessing the effects of vitamin D supplementation on arterial stiffness, a marker of cardiovascular risk, have shown ambiguous results. In a MA including data from seven RCTs involving a total of 547 participants, supplementation with vitamin D3 for 2 to 12 months showed no significant effects on changes in pulse wave velocity [44]. Nor did a MA including data from seven RCTs suggest beneficial effects of vitamin D supplementation on left ventricular function or exercise tolerance [45].…”
Section: Resultsmentioning
confidence: 99%
“…Mendelian randomization studies have reported lower levels of systolic blood pressure among those with genetically lower plasma 25(OH)D concentrations, but the effect sizes of genetically determined differences were very small . Randomized trials of vitamin D and meta‐analyses of trials have shown no significant effect on blood pressure or arterial stiffness . It is unclear whether the null results reflect small sample sizes, insufficient dosing of vitamin D, or the relatively short duration of treatment in such trials.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, recent systematic reviews and meta-analyses concluded that VitD has no effect on markers of arterial stiffness (included RCTs: n = 7 [113]; n = 13 [114]) or markers of endothelial function (included RCTs: n = 16 [112]). In alignment with this narrative review, almost all of the published systematic reviews highlight the significant methodological heterogeneity in terms of dose and duration of treatment, which limits the interpretation of the findings and raises the need for a critical appraisal, over and beyond the reported results.…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%